As potencialidades da palavra : processos de tradução de dramaturgia contemporânea em língua inglesa - Wolff, Manoela Wilhelms (2017)
This master’s dissertation locates itself in a theoretical crossing point that involves cultural, post-colonial, translation and drama studies. Through the analysis and translation of the play Lights Out (1984) by the Indian author Manjula Padmanabhan, we explore and develop the theories brought above as guidelines to help us think about how the translation of dramatic text works. Side by side to our thinking are the words of authors like Gayatri Spivak, Patrice Pavis, Jean-Pierre Sarrazac, Aijiz Ahmad, Edward Said and Beatriz Viégas-Faria, that help us face the complexities of translating a dramatic text written in English language by an Indian woman. In the meanwhile, we also build an historical landscape of Indian theater and argue about the spot of drama studies in our universities and editorial market. Seeking for an otherness in translating we found a great amount of silences and invisibilities and we tried, as far as we could, to bring those realities closer to ours.